2018
DOI: 10.7717/peerj.5602
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a mouse xenograft model of primary colorectal cancer with special reference to perfluorooctane sulfonate

Abstract: Colorectal cancer ranks third among the most commonly diagnosed cancers in the United States. Current therapies have a range of side effects, and the development of a reliable animal model to speed the discovery of safe effective preventative therapies would be of great value. A cross-sectional study in a large Appalachian population recently showed an association between low circulating levels of perfluorooctane sulfonate (PFOS) and a reduced prevalence of colorectal cancer. A study using APCmin (C57BL/6J-Apc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In this study the total successful engraftment rate was 50%, which is comparable to the engraftment rates reported in the studies by Chijiwa et al (58% for gastrointestinal tumors) [ 21 ] and Katsiampoura et al (56% for CRC) [ 11 ]. However, when using surgically removed CRC tumors for engraftment, Katsiampoura et al found an engraftment rate of 72% [ 11 ], which is comparable to the study by Cho et al and Wimsatt et al that reported an engraftment rate of 67% and 64%, respectively [ 20 , 22 ]. When engrafting different types of cancer tissue in CIEA NOG mice, Fujii et al found that CRC tissue had the highest engraftment rate at approximately 32% [ 23 ].…”
Section: Discussionmentioning
confidence: 51%
“…In this study the total successful engraftment rate was 50%, which is comparable to the engraftment rates reported in the studies by Chijiwa et al (58% for gastrointestinal tumors) [ 21 ] and Katsiampoura et al (56% for CRC) [ 11 ]. However, when using surgically removed CRC tumors for engraftment, Katsiampoura et al found an engraftment rate of 72% [ 11 ], which is comparable to the study by Cho et al and Wimsatt et al that reported an engraftment rate of 67% and 64%, respectively [ 20 , 22 ]. When engrafting different types of cancer tissue in CIEA NOG mice, Fujii et al found that CRC tissue had the highest engraftment rate at approximately 32% [ 23 ].…”
Section: Discussionmentioning
confidence: 51%
“…Female BALB/c nude mice (five weeks old) were purchased from Beijing Vital River Laboratory Animal Technology (Beijing, China). The mouse model was established following the previously published protocol [ 22 ]. The mice were randomly assigned to two groups (n=6 per group) to receive HCT116 cells with stable SLCO1B3 knockdown or an equal number of negative controls HCT116 cells by subcutaneous injection into the front flank.…”
Section: Methodsmentioning
confidence: 99%
“…The subcutaneous PDX CRC model is commonly used as it is easy to operate, monitor, and resect with good tumor engraftment, while rarely generate metastases [ 66 ]. In contrast, the orthotopic PDX CRC model is more invasive, labor intensive, and difficult to monitor longitudinally; however, they are better models of metastases because they generate primary tumors and distant lung and liver metastases at similar rates observed in patients [ 64 , 66 , 67 , 68 , 69 ]. As such, orthotopic PDX CRC models are helpful to evaluate local invasive growth of primary tumors, study tumor–host interactions and therapeutic responses in their anatomical context, but preclinical therapeutic studies currently exclusively utilize subcutaneous PDX CRC models [ 70 ].…”
Section: Research Models Crcmentioning
confidence: 99%
“…sive, and difficult to monitor longitudinally; however, they are better models of metastases because they generate primary tumors and distant lung and liver metastases at similar rates observed in patients [64,[66][67][68][69]. As such, orthotopic PDX CRC models are helpful to evaluate local invasive growth of primary tumors, study tumor-host interactions and therapeutic responses in their anatomical context, but preclinical therapeutic studies currently exclusively utilize subcutaneous PDX CRC models [70].…”
Section: Pdx Crc Modelsmentioning
confidence: 99%